Pesan Dakwah Dalam Strategi Komunikasi Public Relations Terhadap Peningkatan Mutu Pelayanan CV. PRASTY MANDIRI - Tetih Sri Mulyati (CV. Multi Kreasi Media, 2022)
The existence of Prasty Mandiri Convection Home Industry which has a good impact on improving the economy of employees and the surrounding community. Initially, the community did not have a job with this business being able to provide job opportunities and could reduce the unemployment rate that occurred in the surrounding environment. The research method used in this study used a qualitative approach with a descriptive type of research. Sources of data used in this study are primary and secondary data. The data analysis technique used went through three stages, namely, data reduction, data presentation, and drawing conclusions. As for checking the validity of the data using observation persistence, increasing persistence, and finally data triangulation. The results of the study show (1) With the role of Prasty Mandiri's Home Industry convection in Tangerang, it will increase the number of workers. In addition, it provides many opportunities for the community, especially in the surrounding villages, and will reduce the unemployment rate and can improve the welfare of the surrounding environment, 2) Efforts to improve the quality of CV services. Prasty Mandiri, able to provide a high economy. With the CV. Prasty Mandiri was able to improve their standard of living which was much better. 3) Constraints and solutions to Prasty Mandiri convection in Tangerang are the many business competitors, money constraints are often faced by these businessmen, usually the price of raw materials rises rapidly and raw materials become scarce, but Prasty Mandiri convection has a solution to overcome this by providing the same model of uniform and raw materials of the same quality or also provide an understanding of price increases to the buyer of the order.